Assessing energy consumption and greenhouse gas emissions in EU member states – decomposition analysis - Jana Chovancová; Lenka Štofejová; Štefan Gavura; Roman Novotný; Martin Rigelský (Entrepreneurship and Sustainability Issues)
This paper addresses the growing global concern regarding energy consumption and its adverse environmental impacts, particularly the increase of greenhouse gas emissions linked to economic development and population growth. To comprehensively assess the environmental implications of energy consumption, a decomposition analysis employing the Index decomposition analysis (IDA) method with the logarithmic mean Divisia index (LMDI) approach was conducted, focusing on the drivers behind energy consumption and greenhouse gas emissions in the EU 27 from 1998 to 2018. This analysis discerns disparities between wealthier and less affluent countries. The findings highlight substantial reductions in greenhouse gas emissions and energy consumption within the EU, primarily attributed to the growing emphasis on reducing the emission intensity targeted by EU policies. Nonetheless, disparities persist among member states, primarily driven by economic activity levels. In relation to the unique economic structures of EU countries results however advocate for diversified approaches tailored to the unique conditions of each Member State to meet the set targets, with an emphasis on fostering collaboration, technology transfer, innovation, and renewable energy adoption to advance sustainability of the region.